A bio-based macromolecular phosphorus-containing active cotton flame retardant synthesized from starch. (15th December 2022) - Lu, Yanfeng; Zhao, Peiyi; Chen, Yajun; Huang, Tiandong; Liu, Yunlan; Ding, Dan; Zhang, Guangxian
Abstract: A novel phosphorus-containing flame retardant, ammonium starch phosphate (ASTP) based on biomass starch, was synthesized for cotton fabrics, and its structure was characterized by 1D and 2D NMR. The limiting oxygen index (LOI) of the cotton fabric treated with 30 % ASTP reached 45.2 %, and the LOI remained at 32.1 % after 50 laundry cycles, indicating that the cotton fabrics treated with ASTP had a high flame retardancy and semi-permanent wash durability. The semi-permanent wash durability, Fourier transform infrared spectroscopy (FT-IR) and the SEM results suggested ASTP was grafted on the surface of cotton fibers by P-O-C covalent bonds. Vertical flammability, the thermogravimetry (TG) and cone calorimetry results showed that the cotton fabrics treated with ASTP had excellent flame retardancy. There were some reductions in the physical properties of the treated cotton fabric. Overall, these results suggested that starch can replace polyhydric alcohols to prepare a more durable formaldehyde-free P-based flame retardants. Graphical abstract: Unlabelled Image